American Association of Clinical Endocrinologists and American College of Endocrinology Guidelines for Management of Dyslipidemia and Prevention of Cardiovascular Disease - Jellinger, Paul S.; Handelsman, Yehuda; Rosenblit, Paul D.; Bloomgarden, Zachary T.; Fonseca, Vivian A.; Garber, Alan J.; Grunberger, George; Guerin, Chris K.; Bell, David S.H.; Mechanick, Jeffrey I.; Pessah-Pollack, Rachel; Wyne, Kathleen; et al. (Endocrine practice, 2017)
The development of these guidelines is mandated by the American Association of Clinical Endocrinologists (AACE) Board of Directors and American College of Endocrinology (ACE) Board of Trustees and adheres with published AACE protocols for the standardized production of clinical practice guidelines (CPGs). Recommendations are based on diligent reviews of the clinical evidence with transparent incorporation of subjective factors, according to established AACE/ACE guidelines for guidelines protocols. The Executive Summary of this document contains 87 recommendations of which 45 are Grade A (51.7%), 18 are Grade B (20.7%), 15 are Grade C (17.2%), and 9 (10.3%) are Grade D. These detailed, evidence-based recommendations allow for nuance-based clinical decision-making that addresses multiple aspects of real-world medical care. The evidence base presented in the subsequent Appendix provides relevant supporting information for Executive Summary Recommendations. This update contains 695 citations of which 203 (29.2 %) are EL 1 (strong), 137 (19.7%) are EL 2 (intermediate), 119 (17.1%) are EL 3 (weak), and 236 (34.0%) are EL 4 (no clinical evidence). This CPG is a practical tool that endocrinologists, other health care professionals, health-related organizations, and regulatory bodies can use to reduce the risks and consequences of dyslipidemia. It provides guidance on screening, risk assessment, and treatment recommendations for a range of individuals with various lipid disorders. The recommendations emphasize the importance of treating low-density lipoprotein cholesterol (LDL-C) in some individuals to lower goals than previously endorsed and support the measurement of coronary artery calcium scores and inflammatory markers to help stratify risk. Special consideration is given to individuals with diabetes, familial hypercholesterolemia, women, and youth with dyslipidemia. Both clinical and cost-effectiveness data are provided to support treatment decisions. 4S = Scandinavian Simvastatin Survival Study A1C = glycated hemoglobin AACE = American Association of Clinical Endocrinologists AAP = American Academy of Pediatrics ACC = American College of Cardiology ACE = American College of Endocrinology ACS = acute coronary syndrome ADMIT = Arterial Disease Multiple Intervention Trial ADVENT = Assessment of Diabetes Control and Evaluation of the Efficacy of Niaspan Trial AFCAPS/TexCAPS = Air Force/Texas Coronary Atherosclerosis Prevention Study AHA = American Heart Association AHRQ = Agency for Healthcare Research and Quality AIM-HIGH = Atherothrombosis Intervention in Metabolic Syndrome With Low HDL/High Triglycerides trial ASCVD = atherosclerotic cardiovascular disease ATP = Adult Treatment Panel apo = apolipoprotein BEL = best evidence level BIP = Bezafibrate Infarction Prevention trial BMI = body mass index CABG = coronary artery bypass graft CAC = coronary artery calcification CARDS = Collaborative Atorvastatin Diabetes Study CDP = Coronary Drug Project trial CI = confidence interval CIMT = carotid intimal media thickness CKD = chronic kidney disease CPG(s) = clinical practice guideline(s) CRP = C-reactive protein CTT = Cholesterol Treatment Trialists CV = cerebrovascular CVA = cerebrovascular accident EL = evidence level FH = familial hypercholesterolemia FIELD = Secondary Endpoints from the Fenofibrate Intervention and Event Lowering in Diabetes trial FOURIER = Further Cardiovascular Outcomes Research with PCSK9 Inhibition in Subjects With Elevated Risk trial HATS = HDL-Atherosclerosis Treatment Study HDL-C = high-density lipoprotein cholesterol HeFH = heterozygous familial hypercholesterolemia HHS = Helsinki Heart Study HIV = human immunodeficiency virus HoFH = homozygous familial hypercholesterolemia HPS = Heart Protection Study HPS2-THRIVE = Treatment of HDL to Reduce the Incidence of Vascular Events trial HR = hazard ratio HRT = hormone replacement therapy hsCRP = high-sensitivity CRP IMPROVE-IT = Improved Reduction of Outcomes: Vytorin Efficacy International Trial IRAS = Insulin Resistance Atherosclerosis Study JUPITER = Justification for the Use of Statins in Primary Prevention: An Intervention Trial Evaluating Rosuvastatin LDL-C = low-density lipoprotein cholesterol Lp-PLA2 = lipoprotein-associated phospholipase A2 MACE = major cardiovascular events MESA = Multi-Ethnic Study of Atherosclerosis MetS = metabolic syndrome MI = myocardial infarction MRFIT = Multiple Risk Factor Intervention Trial NCEP = National Cholesterol Education Program NHLBI = National Heart, Lung, and Blood Institute PCOS = polycystic ovary syndrome PCSK9 = proprotein convertase subtilisin/kexin type 9 Post CABG = Post Coronary Artery Bypass Graft trial PROSPER = Prospective Study of Pravastatin in the Elderly at Risk trial QALY = quality-adjusted life-year ROC = receiver-operator characteristic SOC = standard of care SHARP = Study of Heart and Renal Protection T1DM = type 1 diabetes mellitus T2DM = type 2 diabetes mellitus TG = triglycerides TNT = Treating to New Targets trial VA-HIT = Veterans Affairs High-Density Lipoprotein Cholesterol Intervention Trial VLDL-C = very low-density lipoprotein cholesterol WHI = Women's Health Initiative.